2021
DOI: 10.3390/cancers13133228
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Salmonella into Combination Cancer Therapy

Abstract: Current modalities of cancer treatment have limitations related to poor target selectivity, resistance to treatment, and low response rates in patients. Accumulating evidence over the past few decades has demonstrated the capacity of several strains of bacteria to exert anti-tumor activities. Salmonella is the most extensively studied entity in bacterial-mediated cancer therapy, and has a good potential to induce direct tumor cell killing and manipulate the immune components of the tumor microenvironment in fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 179 publications
(263 reference statements)
0
17
0
Order By: Relevance
“…Once there, they are able to penetrate the desmoplasia from blood vasculature into the hypoxic tumor core, a difficult if not impossible task for most other chemotherapeutics, where they not only lyse the tumor, but act as a potent, life-long reactivation of the immune system against genetically similar tumors [28,191,[193][194][195]. The potential of this particular species is furthered as the fully lytically capable, vegetative form cannot survive in any measurable level of oxygenation such as found in the blood stream or urine, and the spores, which are able to mitigate the toxic effects of oxygen, cannot initiate germination in any physiological level of oxygen, thus alleviating the risk of off-target events [162,187,189,194,196]. Improving the tumor localization capacity of C. novyi through CRISPR-mediated, stable genomic incorporation of an RGD peptide on the spore coat has recently been demonstrated feasible, indicating a promising new direction for customization to elicit better oncolytic capacity [157].…”
Section: Targeting Safety Delivery and Efficacy Of Oncolytic Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Once there, they are able to penetrate the desmoplasia from blood vasculature into the hypoxic tumor core, a difficult if not impossible task for most other chemotherapeutics, where they not only lyse the tumor, but act as a potent, life-long reactivation of the immune system against genetically similar tumors [28,191,[193][194][195]. The potential of this particular species is furthered as the fully lytically capable, vegetative form cannot survive in any measurable level of oxygenation such as found in the blood stream or urine, and the spores, which are able to mitigate the toxic effects of oxygen, cannot initiate germination in any physiological level of oxygen, thus alleviating the risk of off-target events [162,187,189,194,196]. Improving the tumor localization capacity of C. novyi through CRISPR-mediated, stable genomic incorporation of an RGD peptide on the spore coat has recently been demonstrated feasible, indicating a promising new direction for customization to elicit better oncolytic capacity [157].…”
Section: Targeting Safety Delivery and Efficacy Of Oncolytic Bacteriamentioning
confidence: 99%
“…Improving the tumor localization capacity of C. novyi through CRISPR-mediated, stable genomic incorporation of an RGD peptide on the spore coat has recently been demonstrated feasible, indicating a promising new direction for customization to elicit better oncolytic capacity [157]. In contrast, Salmonella and Listeria species not only survive but proliferate in most intracellularly oxygenated environments, increasing the potential risk for off-target toxicity [196]. Salmonella use their flagellated membrane to migrate towards high nutrient concentrations produced primarily within the TME [182][183][184][185].…”
Section: Targeting Safety Delivery and Efficacy Of Oncolytic Bacteriamentioning
confidence: 99%
“…These combinatorial therapies have shown eradication of tumors which may be an outcome of activating radiation-induced tumor cell death. The role of tumor-specific immunity in this context may be investigated further, as a report suggests that the ionizing radiation contributes to immunogenic tumor cell death [ 120 ]. Therapeutic combinations with other existing treatment approaches or interventions have also been reported to enhance the effect of Salmonella -based treatment in modulating tumor-specific immune responses [ 120 ].…”
Section: In Tandem Therapymentioning
confidence: 99%
“…The role of tumor-specific immunity in this context may be investigated further, as a report suggests that the ionizing radiation contributes to immunogenic tumor cell death [ 120 ]. Therapeutic combinations with other existing treatment approaches or interventions have also been reported to enhance the effect of Salmonella -based treatment in modulating tumor-specific immune responses [ 120 ]. For instance, we previously reported that Salmonella treatment did enhance tumor chemosensitivity to cisplatin via Cx43 upregulation [ 121 ].…”
Section: In Tandem Therapymentioning
confidence: 99%
“…Among them, S. Typhimurium has been widely used in cancer treatment due to its specific tumor targeting ability and colonization to overcome the shortcomings of traditional cancer treatments, such as insufficient tumor selectivity and poor tissue penetration. Engineered S. Typhimurium has good biosafety, tumor targeting, and capacity to carry or express anticancer payloads, thereby providing suitable conditions for the combination of BMCT with other therapeutics ( Guo et al, 2020 ; Al-Saafeen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%